A Marriage of Friends or Foes? Radio, Newspapers, and the Facsimile in the 1930s. Issue 3 (2nd July 2016) - Simmons, Charlene
Abstract : The 1930s represent a contentious period between the radio and newspaper industries. In the middle of the press-radio war, a new technology, the broadcast radio facsimile, emerged with the potential to bring together the warring industries. Although the radio facsimile was short lived, its story, seen through the lens of the press-radio war, provides an interesting look at the forces shaping a new technology. Envisioned as a technology that would allow subscribers to receive the newspaper via a radio receiver, the facsimile presented an interesting dilemma: Who would control the creation and dissemination of news—the newspaper or radio industry? This article explores this question through an examination of industry narratives about the facsimile. In analyzing the discourses, this study focuses on how the newspaper and radio industries envisioned the future of the facsimile. Was the facsimile viewed as a means for cooperation or as a point of contention?